Inhibitory actions of electrolysed water on food spoilage fungi - Wohlgemuth, Franziska (2022)
Chemical sanitisers are needed for controlling microbial contamination and growth in various settings, including healthcare, domestic settings and the food industry. One promising sanitiser with proposed applications in the food industry is the oxidising sanitiser electrolysed water (EW). For EW applications to be effective, a more in-depth understanding of EW mode-of-action is needed, together with the identification of limiting factors associated with the chemical matrices in relevant EW applications.